Pengaruh Lingkungan Kerja Dan Fleksibilitas Kerja Terhadap Komitmen Organisasi Pada Driver Maxim - Reichan Maulana Putra Isna; R. Deni Muhammad Danial; Resa Nurmala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of the work environment and work flexibility on organizational commitment (an empirical study on 5 Maxim-bike Driver Communities in Sukabumi City). The research approach used is a quantitative approach. Multistage Cluster Sampling sampling method. The samples taken were 63 respondents in 5 communities. The results of this study indicate that the work environment has a positive and significant influence on organizational commitment and work flexibility also has a positive and significant influence on organizational commitment in the 5 Maxim-bike Diver Communities in Sukabumi City. Keywords: work environment, work flexibility, organizational commitment, Maxim